Narrative on Hydrogen Therapy and its Clinical Applications: Safety and Efficacy - Ahmad, Aqeel; Baig, Atif A.; Hussain, Mubashir; Saeed, Muhammad Usama; Bilal, Muhammad; Ahmed, Naveed; Chopra, Hitesh; Hassan, Muhammad; Rachamalla, Mahesh; Putnala, Sravan Kumar; Khaliq, Muniba; Tahir, Zirwah; et al. (Current Pharmaceutical Design, 2022)
Molecular hydrogen proved itself as a novel therapeutic candidate and has been thriving from the beginning with its potential clinical significance, higher affinity, and cellular integrity and permeability. Hydrogen Therapy (HT) has gained scientists' attention with the proven clinical ability to attenuate chronic inflammation, diminish oxidative stress, restrict apoptosis, minimize cellular injury, and refine tissue functioning. Therapeutic Implementation of H2 for disease prevention and treatment is a newly emerging field with limited knowledge available on formulations, tissue-specific effects, efficacy, and safety. This article will discuss HT's therapeutic potential for its efficacy and safety in cardiovascular, respiratory, hematological, metabolic, infectious, and neurodegenerative disorders. In addition to this, the molecular mechanisms and nanotechnological implications of hydrogen therapy will be discussed in detail. Finally, the article will provide insight into advancements and automation, future perspectives, and recommendations. There is a need to study and conduct higher-scale trials targeting personalized treatments under molecular and genetic vitals.
Keywords: reducing agent